Organization of professional preparation of trainer-teacher to future professional activity in higher educational establishments of Ukraine. - Svatyev A.V (Kharkov National Pedagogical University, 2011)
The problem of professional preparation of trainer-teacher is considered in a pedagogical theory. On the basis of analysis of literature and realizable research some features of organization of professional preparation of trainer-teacher are found out to future professional activity in higher educational establishments. Data of the questionnaire questioning of students of higher educational establishments of Ukraine are used in research. Expediency and actuality of select problem of research is well-proven. Authorial vision of decision of questions of professional preparation of specialists of the noted direction is offered.